2010
DOI: 10.1002/chem.201000284
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of β‐Hydroxy‐α‐Amino Acid Derivatives via Direct Catalytic Asymmetric Aldol Reaction of α‐Isothiocyanato Imide with Aldehydes

Abstract: An easily available and efficient chiral N,N'-dioxide-nickel(II) complex catalyst has been developed for the direct catalytic asymmetric aldol reaction of alpha-isothiocyanato imide with aldehydes which produces the products in morderate to high yields (up to 98 %) with excellent diastereo- (up to >99:1 d.r.) and enantioselectivities (up to >99 % ee). A variety of aromatic, heteroaromatic, alpha,beta-unsaturated, and aliphatic aldehydes were found to be suitable substrates in the presence of 2.5 mol % L-prolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 106 publications
0
9
0
Order By: Relevance
“…[22] Other groups reported similar aldol condensation reactions by using alternative nucleophilic species, such as the 5-alkoxyoxazole developed by Evans and co-workers [23] and, more recently, the a-isothiocyanato imides developed by Feng's group (31, Scheme 11). [24] Fengs route is not air-sensitive, applicable to a wide range of aldehydes, and proceeds with excellent diastereoselectivity and enantioselectivity.…”
Section: Asymmetric Aldol Condensation With Chiral Catalystsmentioning
confidence: 98%
See 1 more Smart Citation
“…[22] Other groups reported similar aldol condensation reactions by using alternative nucleophilic species, such as the 5-alkoxyoxazole developed by Evans and co-workers [23] and, more recently, the a-isothiocyanato imides developed by Feng's group (31, Scheme 11). [24] Fengs route is not air-sensitive, applicable to a wide range of aldehydes, and proceeds with excellent diastereoselectivity and enantioselectivity.…”
Section: Asymmetric Aldol Condensation With Chiral Catalystsmentioning
confidence: 98%
“…The aldol reaction of aromatic aldehydes produced syn adducts, whereas the reaction of aliphatic aldehydes exclusively gave the anti adducts. Hydrolysis of the isolated aldol adducts afforded the corresponding b-hydroxy-a-amino acids (24) in good yields with excellent optical purity.…”
Section: Camphor Auxiliarymentioning
confidence: 98%
“…Since the 2000s, the use of α‐isothiocyanato derivatives has become the focus of research to access these products in a number of asymmetric reactions promoted by metal complexes and organocatalysts. Several research groups including ours,5d,6e have reported the addition of α‐isothiocyanato derivatives to CO,5 CN6 and CC7 bonds. For example, the Willis group reported chiral bis(oxazoline)–Mg(ClO 4 ) 2 complexes‐catalyzed reactions of aldehydes5b and aldimines 6a.…”
Section: Introductionmentioning
confidence: 97%
“…As a privileged chiral scaffold, chiral N , N′ ‐dioxide–metal complexes have been successfully applied in many asymmetric transformations 10. On the basis of our recent efforts to expand the utilization of such chiral ligands, we realized the aldol cyclization reaction5d of both β,γ‐unsaturated α‐keto esters and aryl‐substituted α‐keto esters with α‐isothiocyanato imide. A readily available chiral N , N′ ‐dioxide–Y(OTf) 3 (Tf=triflate) complex system was efficient, giving chiral cyclic thiocarbamates bearing a chiral quaternary stereocenter in good to high yields, excellent diastereo‐ (up to 25:1 dr ) and enantioselectivities (up to 99% ee ).…”
Section: Introductionmentioning
confidence: 99%
“…To reveal the parent β-hydroxy-α-amino acids or esters, however, strongly acidic conditions are required and auxiliary-derived by-products can complicate isolation of the products. [26e, 26f] Evans and Weber developed α-isothiocyanato acyl oxazolidinones as substrates in their diastereoselective tin-mediated aldol chemistry, [28] and notable advances have been recorded by the Willis, [29] Feng, [30] and Seidel [31] groups to transform this method into processes mediated by chiral catalysts. These α-isothiocyanate methodologies afford thiocarbamate heterocycles as products, which conveniently serve to protect the amine and alcohol functionalities of the aldol adducts, but require a 3-step procedure to reveal the embedded α-amino acids.…”
mentioning
confidence: 99%